2008
DOI: 10.1124/dmd.107.018234
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of [14C]Dasatinib: In Vitro Studies in Rat, Monkey, and Human and Disposition after Administration to Rats and Monkeys

Abstract: ABSTRACT:This study describes the in vitro metabolism of [ 14 C]dasatinib in liver tissue incubations from rat, monkey, and human and the in vivo metabolism in rat and monkey. Across species, dasatinib underwent in vitro oxidative metabolism to form five primary oxidative metabolites. In addition to the primary metabolites, secondary metabolites formed from combinations of the oxidative pathways and conjugated metabolites of dasatinib and its oxidative metabolites were also observed in hepatocytes incubations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
(32 reference statements)
1
36
1
1
Order By: Relevance
“…4; Table 3). The difference in the bile and fecal profiles was attributed to hydrolysis of the conjugative metabolites in the gastrointestinal tract before excretion in the feces (Parker et al, 1980;Christopher et al, 2008). M6, which was FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4; Table 3). The difference in the bile and fecal profiles was attributed to hydrolysis of the conjugative metabolites in the gastrointestinal tract before excretion in the feces (Parker et al, 1980;Christopher et al, 2008). M6, which was FIG.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that glucuronides typically undergo hydrolysis in the gastrointestinal tract by gut flora before excretion in the feces (Parker et al, 1980;Christopher et al, 2008). Therefore, the current studies included administration of […”
mentioning
confidence: 99%
“…An additional 14% of the dose was recovered in feces, suggesting direct intestinal secretion of drug-derived radioactivity (Christopher et al, 2008a).…”
mentioning
confidence: 96%
“…Studies have shown that dasatinib was extensively metabolized in animals and humans (Christopher et al, 2008a,b). The primary pathways of metabolism included N-dealkylation (M4), N-oxidation (M5), carboxylic acid formation (M6), and hydroxylation (M20 and M24) (Christopher et al, 2008a). Based on the human absorption, distribution, metabolism, and excretion (ADME) study with […”
mentioning
confidence: 99%